Geran insentif penyeliaan - UiTM Shah Alam, Akademi Pengajian Bahasa (Academy of Language Studies, 2022)
Geran Insentif Penyeliaan (GIP) is an initiative by Universiti Teknologi MARA (UITM) that offers financial support to postgraduate students throughout their study. The aim of this grant is to enhance synergy between supervisors and postgraduates. A successful recipient of GIP, Dr Rozaimah Rashidin, alongside her postgraduate student, Nor Umiumairah Mohamad, an LG750 student, were awarded RM18,000 for their project entitled 'Analysis Semantik Inkuisitif Perlambangan Dalam Peribahasa Melayu'. We highly value the team's diligent work and would like to relay our heartfelt congratulations for their achievement.